IRON DYNAMICS AND ITS RELATION TO SOIL REDOX POTENTIAL AND PLANT GROWTH IN ACID SULPHATE SOIL OF SOUTH KALIMANTAN, INDONESIA - Wahida Annisa; Dedy Nursyamsi (Indonesian Journal of Agricultural Science, 2016)
Organic matter has a function to maintain reductive conditions and to chelate toxic elements in acid sulphate soils. The study aimed to assess the dynamics of ferrous iron (Fe2+) in acid sulphate soil and its correlation with soil redox potential (Eh) and plant growth. The experiment was arranged in two factorial randomized block design with three replications. The first factor was two types of organic matter: (1) control (without organic matter), (2) rice straw and (3) rush weed (Eleocharis dulcis). The second factor was time of decomposition of organic matter: I1 = 2 weeks, I2 = 4 weeks, I3 = 8 weeks, and I4 = 12 weeks (farmer practice). The results showed that concentration of ferrous iron in the soil ranged from 782 to 1308 mg kg-1 during the rice growing season. The highest constant rate of iron reduction (k F2+) was observed on application of rice straw and rush weed with decomposition time of 8 weeks with the k Fe2+ value of 0.016 and 0.011 per day, respectively, while the ferrous iron formation without organic matter had the k Fe2+ value of 0.077 per day. The ferric iron (Fe3+) reduction served as a function of soil Eh as indicated by the negative correlation of ferrous iron and Eh (r = -0.856*). Organic matter decreased exchangeable iron due to chelating reaction. Iron concentration in roots was negatively correlated with soil soluble iron (r = -0.62*). Application of rice straw decomposed for 8 weeks increased the height of rice plant up to 105.67 cm. The score of Fe2+ toxicity at 8 weeks after planting ranged from 2 to 3, so rice crop did not show iron toxicity symptoms.